Purinergic signaling modulates human visceral adipose inflammatory responses: implications in metabolically unhealthy obesity. Issue 5 (25th February 2015) - Pandolfi, J; Ferraro, A; Lerner, M; Serrano, J R; Dueck, A; Fainboim, L; Arruvito, L
Abstract : Purinergic signaling is a novel mechanism involved in maintaining the chronic inflammation of visceral adipose tissue underlying the metabolic changes in obesity. Abstract: Obesity is accompanied by chronic inflammation of VAT, which promotes metabolic changes, and purinergic signaling has a key role in a wide range of inflammatory diseases. Therefore, we addressed whether fat inflammation could be differentially modulated by this signaling pathway in the MUO and in individuals who remain MHO. Our results show that the necrotized VAT of both groups released greater levels of ATP compared with lean donors. Interestingly, MUO tissue SVCs showed up-regulation and engagement of the purinergic P2X7R. The extracellular ATP concentration is regulated by an enzymatic process, in which CD39 converts ATP and ADP into AMP, and CD73 converts AMP into adenosine. In VAT, the CD73 ectoenzyme was widely distributed in immune and nonimmune cells, whereas CD39 expression was restricted to immune CD45PAN + SVCs. Although the MUO group expressed the highest levels of both ectoenzymes, no difference in ATP hydrolysis capacity was found between the groups. As expected, MUO exhibited the highest NLRP3 inflammasome expression and IL-1β production. MUO SVCs also displayed up-regulation of the A2AR, allowing extracellular adenosine to increase IL-1β local secretion. Additionally, we demonstrate that metabolic parameters and BMI are positively correlated with purinergic components in VAT. These findings indicate that purinergic signaling is a novel mechanism involved in the chronic inflammation of VAT underlying the metabolic changes in obesity. Finally, our study reveals a proinflammatory role for adenosine in sustaining IL-1β production in this tissue.